The Moderation Role of Innovation Management and the Mediation Role of TQM practices on the Relationship between Entrepreneurial Leadership and Organizational Performance of Kuwait SMEs - Fahad Awad Aber Sawaean Alenezi, Khairul Anuar Mohd. Ali (International Journal of Advanced Science and Technology, 2020)
Small and medium enterprises (SMEs) in Kuwait are facing an ever increasing competition at the national level in addition to the wide variety of problems that have to be resolved in order to attain and ensure long-term success and enhanced performance. The present paper aims to describe the association of the determinants of organizational performance, including entrepreneurial leadership (EL), total quality management (TQM) practices, and innovation management (IM), of Kuwait SMEs. However, only a small number of studies have offered a comprehensive model for elucidating the association of EL, TQM and IM with SMEs performance. Hence, this study addresses the research gap by proposing a conceptual model to illustrate the relationships between these variables. The present study adopts a quantitative approach, where data was gathered by administering of a survey questionnaire. The questionnaire was sent to 500 SME owners and CEOs and a total of 384 usable questionnaires were collected from the subjects. Results of this study show that entrepreneurial leadership has a positive and significant effect on organizational performance. The mediating effect of TQM practices is significant in the association of entrepreneurial leadership with performance; furthermore, innovation management was also found to be a significant moderator in the same relation.